آراء تشومسكي في اكتساب اللغة والاستفادة منها في تعليم اللغة العربية للناطقين بغيرها - sammy, suriyani; Muhammad Nashirudin; Muhammad Nanang Qosim; Edy Saputra ('ARABIYYA: JURNAL STUDI BAHASA ARAB, 2023)
The research in this study seeks to highlight the cognitive process of modern linguistic thought. It concerns Chomsky's views on the acquisition of language. The aim of this research is to benefit from the teaching of the Arabic language to its non-Arabic speakers. The approach in this study was a qualitative approach, and the research data included primary data and secondary data related to the analysis of Chomsky theory in the acquisition of language, and the results of the analysis were: 1. Providing cognitive theories with appropriate information on how the learner adjusts the learn process and the acquisition of the second language. The understanding of what is answered at the beginning of the education, so that learners are able to control the learning process, to become automatic or mechanism, so the learner needs a suitable opportunity, to activate strategies for the collection of knowledge. 2. The formation of the language environment, which should be in the teaching of the second language as it is a means to achieve the goal in the teaching of the second language acquisition, especially in the first stage. And that the linguistic environment is one of the means to achieve a goal in the teaching of the second language, as Chomsky explained in his theory that the acquisition of language is instinct, because anyone living in a particular environment will acquire this language naturally.